2011
DOI: 10.1021/la201914h
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Choline-like Ionic Liquids: Their Penetration Ability through Cell Membranes and Application to SEM Visualization of Hydrous Samples

Abstract: This letter proposes the use of choline-like hydrophilic ionic liquids (ILs) to visualize hydrous samples (e.g., seaweed and other biological or food samples) for scanning electron microscopy (SEM) observation. Some of the water in the samples was successfully replaced with these ILs, which penetrated the cell membranes. The treated samples did not contract much even after drying. The ILs' ionic conductivity decreased the charging of sample surfaces, and good SEM images were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…In addition to this, we found that a thin RTIL layer spread on insulating materials works as a conductive layer like a thin Au layer when such materials are observed by using a common SEM system [10][13]. Since our first report [9], a number of similar works have been reported by various research groups [14][20].…”
Section: Introductionsupporting
confidence: 69%
“…In addition to this, we found that a thin RTIL layer spread on insulating materials works as a conductive layer like a thin Au layer when such materials are observed by using a common SEM system [10][13]. Since our first report [9], a number of similar works have been reported by various research groups [14][20].…”
Section: Introductionsupporting
confidence: 69%
“…It has been known recently that IL possess ionic conductivity and lack electric conductivity which makes them quite suitable for SEM observation giving contrast images without noise, and keeps the sample in wet condition shown in Fig. 8, Panel B and C [61,62]. At CMC (100 mM) the size of the vesicles increases largely and the BMOP forms a film around the gramicidin vesicle, this type of behaviour of the pyrrolidinium based IL with vesicles has been reported earlier [23].…”
Section: Fesem Characterizationsupporting
confidence: 63%
“…In a highly innovative application, Kawai et al 314 prepared several choline-like hydrophilic ILs (hydroxyl- and/or carboxyl-functionalized ammonium ILs with CH 3 SO 3 − as the anion), and showed their potential for visualizing samples by scanning electron microscopy (SEM), including hydrated samples such as seaweed and foodstuffs. It was found that this sample treatment prior to SEM analysis allows for the visualization of samples without charging and without metal sputtering.…”
Section: Applications Of Ether- and Hydroxyl-functionalized Ilsmentioning
confidence: 99%